Negotiating skills - Hindle, Tim (Essential managers, 1998)
This is a reference book on minimizing stress, for all those in, or aspiring to a position of responsibility, with a focus on developing and enhancing professional management practice. Illustrated examples, charts and flow diagrams reveal practical techniques for handling real-life situations. FDEA